Being rational reflected in cecelia ahern p.s. i love you novel (2004): an individual psychological approach - Hastuti, Eva, Dr. M. Thoyibi, M.S, Mauly Halwat Hikmat, Ph. D (2014)
The objective of the research is to analyze the novel based on individual psychological proposed by Alfred Adler. This research paper belongs to qualitative research. The method to analyze this data is descriptive analysis. The researcher comes to the conclusions as follows. Based on the individual psychological analysis, Cecelia Ahern illustrates a psychological phenomenon in which an individual was too emotional and influenced by the past life, particularly by the mental life. In this novel the author suggests peoples should be rational to face reality of life. The author portrays strength of Holly Kennedy to cope with her problem after her husband died. She uses her creativity to heal herself. She also arranges her striving for superiority to provide her inferiority feeling to create fictional finalism.